(untitled) (Scientia Agricola, 2020)
Cost and environmental restrictions limit the use of fishmeal (FM) in aquafeeds and plant protein (PP) sources. Soybean by-products are important alternative; however, their antinutritional factors may reduce fish growth. This study evaluates the effect of FM substitution for PP (soybean meal and soy protein concentrate) in diets of dourado (Salminus brasiliensis), a promising species for fish farming and empirically considered highly tolerant to PP-based diets. A control diet was formulated to contain 20 % of fishmeal and 61 % of plant protein (SBM) and other five diets with decreasing FM graded levels (16 %, 12 %, 8 %, 4 %, 0 %), which were replaced by soybean protein concentrate (SPC), comprising six treatments and four replicates. Fifteen dourados (6.73 ± 0.2 g) were stocked into 200 L tanks in a recirculating system, fed with experimental diets three times a day to apparent satiation for 90 days. Growth performance, food conversion ratio, protein efficiency ratio and protein retention efficiency of fish were impaired when FM substitution exceeded 13.05 % (the broken line analysis method). Histological analysis of intestinal mucosa showed a decrease in villus height when fishmeal was totally replaced by PP, which probably impaired digestive functions of fish and reflected in a severe loss on growth performance.